Unmasking the curve: is growth hormone therapy a silent contributor to pediatric scoliosis: a systematic review - Gonçalves Moreira, Vinícius Ribamar; Rotondano Filho, Adriano Ferro; Custódio Júnior, Edimar Gomes; Gonçalves Barbosa, Rafaela (International Journal of Research in Orthopaedics, 2025)
Growth hormone (GH) therapy is used to promote growth in pediatric short stature conditions, including idiopathic short stature (ISS), growth hormone deficiency (GHD), and Turner syndrome. Concerns have arisen regarding potential associations between GH treatment and the development or progression of scoliosis, particularly when used off-label in ISS. A systematic review following PRISMA guidelines was conducted and registered in PROSPERO (CRD420251069349). Searches were performed across PubMed, Scopus, Embase, and Web of Science through July 2025. Studies evaluating scoliosis onset or progression during GH therapy in children were included. Data extracted encompassed GH dosage, treatment duration, patient demographics, scoliosis incidence, Cobb angle progression, and orthopedic outcomes. Quality assessments were performed using the Newcastle‑Ottawa Scale, Cochrane Risk of Bias, and AMSTAR‑2 tools. Studies involving over 3,000 children were analyzed. Scoliosis incidence ranged from 3% to 22%, with higher risk among boys, those experiencing rapid growth velocity, and syndromic conditions like Turner and Prader–Willi. Ziv‑Baran et al reported a hazard ratio of 2.12 (95% CI: 1.75–2.57; p<0.001) for scoliosis in GH-treated versus controls. Evidence from clinical and animal studies suggests that GH stimulates asymmetric vertebral growth via the GH/IGF‑1 axis. Although most scoliotic curves were mild and non-surgical, regular orthopedic surveillance was recommended. GH therapy in children, particularly for off-label ISS use, may increase risk for scoliosis onset or progression in at-risk subgroups. While overall orthopedic risk is low, early identification of predisposed patients and periodic radiographic monitoring-especially during rapid growth phases-is essential to ensure safe and individualized GH treatment.